Determinant Performance of Tax Examiners in KPP Pratama South Sulawesi - Ulfa Rabiyah; Kartini Hanafi; Andi Kusumawati; Aini Indrijawati (IECON: International Economics and Business Conference, 2023)
This study aims to examine and analyze the effect of professionalism, emotional stability and self- esteem on the performance of tax examiners at KPP South Sulawesi. Theories and concepts in this study are attribution theory and personality theory. The data analysis technique used in this study is multiple linear regression. Data quality testing uses validity and reliability tests, and classic assumption tests. The test results show that professionalism affects the performance of tax auditors, emotional stability affects the performance of tax auditors and self-esteem affects the performance of tax auditors. The higher the professionalism, emotional stability and self-esteem, the higher the performance of the tax examiner in completing tax audits at KPP in South Sulawesi.